2014
DOI: 10.1093/gerona/glu093
|View full text |Cite
|
Sign up to set email alerts
|

Regional Cerebral Glucose Metabolism and Gait Speed in Healthy Community-Dwelling Older Women

Abstract: The normalized-rCMRglc values in specific regions were associated with individual differences in gait function, even in healthy older women. These regions of the cerebrum could play an important role in gait control. Understanding the cerebral glucose metabolism in these brain regions may enable early detection of mobility limitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 41 publications
3
35
0
Order By: Relevance
“…The approach employed and the results obtained in the present study are considered to endorse these previous reports. Furthermore, various previous reports [17][18][19][20][21] have suggested an association between changes in exercise speed and improvement in brain function. These findings suggest that physical training that involves being aware of the focused attention (as adopted in this intervention method) is more likely to lead to higher brain activity and improvement in cognitive function than monotonous physical training.…”
Section: Discussionmentioning
confidence: 92%
“…The approach employed and the results obtained in the present study are considered to endorse these previous reports. Furthermore, various previous reports [17][18][19][20][21] have suggested an association between changes in exercise speed and improvement in brain function. These findings suggest that physical training that involves being aware of the focused attention (as adopted in this intervention method) is more likely to lead to higher brain activity and improvement in cognitive function than monotonous physical training.…”
Section: Discussionmentioning
confidence: 92%
“…Other neuroimaging studies have linked functional brain networks during rest with single-task gait (Sakurai et al 2014) and dual-task gait (Yuan et al 2015). The first study found that cerebral glucose metabolism in the PFC, PCC, and parietal cortex was associated with single-task gait and these regions were thought to be constitutive parts of the default mode network (Sakurai et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The first study found that cerebral glucose metabolism in the PFC, PCC, and parietal cortex was associated with single-task gait and these regions were thought to be constitutive parts of the default mode network (Sakurai et al 2014). The second study found that dual-task gait was associated with greater connectivity in dorsolateral prefrontal regions of the left fronto-parietal resting state network (Yuan et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study indicated that regional cerebral metabolic rates of glucose (rCMRglu) in the prefrontal cortex were associated with control of gait speed . Another recent cross‐sectional study reported that slower maximum walking speed was associated with lower rCMRglu in the prefrontal, posterior cingulate, and parietal cortices, independent of major health factors …”
Section: Discussionmentioning
confidence: 99%